Pre-School Religious Education According to the Qur'an Course Teachers: The Mus Province Example - Karasu, Teceli (ATATURK UNIV, FAC THEOLOGY, 2019)
In accordance with the protocol jointly assigned by the Ministry of National Education and Presidency of Religious Affairs, the teachers of Qur'an courses are assigned to preschool education. The reason for this research is the lack of a detailed study on this activity carried out to meet students' religious development needs. The aim of this study is to reveal the nature of the activities performed by those who were assigned in preschool education under the Ministry of National Education. For this purpose, interviews were held with 12teachers who were assigned to preschool education in Mus city center within the scope of D group Schedule of Qur'an Courses. The data of this study, which was prepared in a qualitative design, were collected through the interview form with semi-structured questions. Before putting the last touches on the form, literature was reviewed, and educational environment was observed. The main weak points of the teachers are not knowing the developmental characteristics of the students well and not being able to properly adapt a topic to their levels. It is also seen that some of the goals in the curriculum are above the students' levels and that in education priority is given only to reading Qur'an.
Keywords: Qur'an Course Teacher; Religious Education; Pre-school education; Qur'an Course